Commercially available novel device to prevent the diffusion of droplets from subjects undergoing esophagogastroduodenoscopy: A pilot study with its prototype. Issue 1 (1st September 2021) - Endo, Hiroyuki; Koike, Tomoyuki; Obara, Noriyuki; Hatta, Waku; Masamune, Atsushi
Abstract: Introduction: Under the current pandemic situation of the coronavirus disease 2019 (COVID‐19), we have newly developed a commercially available device named Endomask to prevent the diffusion of droplets from subjects undergoing esophagogastroduodenoscopy (EGD). Herein, we evaluate the efficacy and safety of the device, and also evaluate the stress of the device on the operators and the subjects of EGD. Methods: The efficacy of the device was evaluated using an experimental model that simulated the environment of EGD. The safety of the device was evaluated clinically by means of measuring the oxygen saturation and the expiratory carbonic dioxide partial pressure of subjects with our device during EGD. The stress of the device on the operability of the endoscopists and the respiration of the subjects were evaluated using questionnaires. Results: In the experiments with Endomask, the percentage of the area with simulated droplets was significantly reduced compared to that without our device (median, 0.24% vs. 6.96%, p  = 0.009). The saturation of oxygen and the expiratory carbonic dioxide partial pressure of subjects with the device did not show significant change at any recording times. Neither the operators nor the subjects felt serious stress from examination with the device. Conclusions: Endomask could remarkably and safely prevent the diffusion of droplets without serious stress. Endomask is expected to contribute to a reduction of the infectious risk of SARS‐CoV‐2 in endoscopy units during COVID‐19 pandemic.